The Menace of Antimicrobial Resistance - Gupta, Pratima; Deka, Sangeeta (Indian Journal of Community Health, 2018)
The discovery of Penicillin in 1926 was followed by discovery and use of several groups of antimicrobials, which gave a major boost to modern medicine by significantly decreasing mortality and morbidity. Thus, antimicrobials were regarded as a major breakthrough as they not only cured infectious diseases but also played a key role in success of advanced medical practices viz organ transplant, immunosuppressive therapy, cancer chemotherapy, complicated surgeries specially in contaminated areas, implants etc. However these ‘miracle drugs’ are slowly losing their efficacy due to emergence and spread of antimicrobial resistance (AMR). [1-3] Emergence of AMR is a natural evolutionary phenomenon shown by microorganisms against widespread use of antimicrobials. Beta lactams were the first affected group (Table-1) and since then bacteria have gained resistance to other groups of -antibiotics too. None of the classes including even the recently discovered antibiotics have been able to escape this dynamic phenomenon. [3-6]